Factors related to outcome of anterior cruciate ligament reconstruction rehabilitation in male: fear of re-injury, quality of life and patient education / Rohani Haron - Haron, Rohani (Institute of Research, Development and Commercialization (IRDC), 2016)
There have been very limited studies conducted on subjective outcome with regard to psychological factor, quality of life (QOL) and patient education after anterior cruciate ligament reconstruction (ACLR) rehabilitation among male involved in recreational activities. This study investigated fear of re-injury, QOL and patient education after ACLR rehabilitation. The purposes were (1) to determine the correlation between fear of re-injury and functional activity performance; (2) to determine the correlation between QOL, fear of re-injury and functional activity performance; (3) to identify the determinants of QOL concerning patients’ background, fear of re-injury and functional activity performance; (4) to explore patients’ experience in patient education by patient- physiotherapist face-to-face interaction on ACLR rehabilitation; and (5) to explore patients perception of patient education related to QOL after ACLR rehabilitation. A cross-sectional survey was conducted on 60 participants recruited by convenient sampling. They completed background information form, IKDC, KOOS and Lysholm, Tanpa Scale of Kinaesiophobia and ACL-QOL after 14 to 16 weeks of ACLR rehabilitation. Data were analysed by Pearson and Spearman correlation including multiple linear regression. For phenomenological design, interview guide was used to conduct interviews on 10 participants taken by purposive sampling…